Konseling Teknik Rehearsal Kekuatan Husnudzon Untuk Mereduksi Kecemasan Public Speaking - Salmaeka, Fadhilah; Sutanti, Tri (JURNAL KONSELING GUSJIGANG, 2024)
Anxiety during a presentation in front of the class is a condition where a person experiences fear or worry because they have to speak in front of others, either imagining or doing the presentation. Based on the observations conducted at SMA Negeri 2 Cilacap, anxiety was commonly associated with the students' negative perceptions of themselves and others. Hence, individual counseling services with rehearsal techniques emphasizing the concept of husnuzon were conducted to reduce the student's anxiety during a presentation in front of the class in SMA Negeri 2 Cilacap. The research employed a pre-experimental type with a quantitative approach and pretest-posttest one-group design. Three students were the study’s subjects. Purposive sampling is the method of sample elimination used, while the data were analyzed using descriptive statistic techniques. The scores indicated a significant difference in the anxiety level during the presentation before and after the individual counseling.